2003
DOI: 10.1093/jis/3.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Practical uses for ecdysteroids in mammals including humans: and update

Abstract: Ecdysteroids are widely used as inducers for gene-switch systems based on insect ecdysteroid receptors and genes of interest placed under the control of ecdysteroid-response elements. We review here these systems, which are currently mainly used in vitro with cultured cells in order to analyse the role of a wide array of genes, but which are expected to represent the basis for future gene therapy strategies. Such developments raise several questions, which are addressed in detail.First, the metabolic fate of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
117
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 176 publications
4
117
0
10
Order By: Relevance
“…[4] As a consequence of their ability to mimic the actions of arthropod moulting hormones while being non-toxic to vertebrates, phytoecdysteroids are interesting lead compounds for the development of environmentally friendly invertebrate pest control agents. [5] Furthermore, steroidal and non-steroidal ligands for natural and mutated EcRs have been used successfully in EcR-based inducible gene expression systems for the modulation of the expression of a gene of interest within a host cell [6] and animal models. [7] Geneswitch technology finds applications in several fields of the life sciences, including functional genomics, drug discovery and gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[4] As a consequence of their ability to mimic the actions of arthropod moulting hormones while being non-toxic to vertebrates, phytoecdysteroids are interesting lead compounds for the development of environmentally friendly invertebrate pest control agents. [5] Furthermore, steroidal and non-steroidal ligands for natural and mutated EcRs have been used successfully in EcR-based inducible gene expression systems for the modulation of the expression of a gene of interest within a host cell [6] and animal models. [7] Geneswitch technology finds applications in several fields of the life sciences, including functional genomics, drug discovery and gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The non-hormonal biological activity of ecdysteroids towards mammals is intensively studied [4][5][6]. It has been reported that non-polar ecdysteroids possess chemo-sensitizing activity towards various cancer cell lines [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Some ecdysteroids act as hormone antagonists, disturbing insect molting process [2]; however, these compounds cannot efficiently affect the population of insects, which has acquired defense mechanisms against exogenous ecdysteroids during evolution. In view of this fact, a synthesis of novel ecdysteroid analogues would provide compounds for efficient regulation of vital processes in insects [3].The non-hormonal biological activity of ecdysteroids towards mammals is intensively studied [4][5][6]. It has been reported that non-polar ecdysteroids possess chemo-sensitizing activity towards various cancer cell lines [7][8][9][10].…”
mentioning
confidence: 99%
“…It was found that ecdysteroids are nontoxic for warm-blooded animals. Versatile physiological effect of ecdysteroids on humans and animals was revealed: they were found to control mineral, carbohydrate, lipid, and protein exchange, normalize sugar and cholesterol concentration in blood, stimulate hemopoietic activity, and exert immunomodulatory effect [3]. The diversity of physiological action of ecdysteroids is determined to some extent by their antioxidant properties, for many diseases are related to oxidative stress [4].…”
mentioning
confidence: 99%
“…On the other hand, the substituents on C 2 and C 3 in the 1,3-dioxolane ring of the 2,3-acetal moiety differ only slightly, and the C 2″′ chiral acetal carbon atom gives only one peak in the 13 C NMR spectrum. Protons at the C 2″′ and C 2″″ acetal carbon atoms in V resonated in the 1 H NMR spectrum as broadened singlets (w 1/2 = 13 Hz) at δ 5.18 (20,22) and 5.24 ppm (2,3).…”
mentioning
confidence: 99%